Revisiting the association between transportation noise and heart disease reported in the World Health Organization Environmental Noise Guidelines for the European Region: a systematic review and meta-analysis - Michaela Minkin; Lisa Woodland; Owen A. Williams; Sophie Hamilton; Anna L. Hansell; Danielle Vienneau; Xiangpu Gong; Benjamin Fenech (Environment International, 2025)
Background: Whilst the link between long-term exposure to transportation noise and cardiovascular disease has been discussed for several decades, there are still uncertainties in the exact quantitative relationship between the two. A systematic review and meta-analysis that informed recommendations in the World Health Organization Environmental Noise Guidelines for the European Region included studies published up to 2015. Since then, there has been a rapid increase in publications from epidemiological studies exploring the risk over a larger noise exposure range, and with more precise exposure assignment. Given the influential nature of the WHO Guidelines, we investigated whether the inclusion of studies published up to December 2023 changes the quantitative relationship. Methods: We carried out a systematic review and meta-analysis on the association between transportation noise (road, rail, and aircraft) and heart disease, specifically ischaemic heart disease (ICD-10 I20-25), atrial fibrillation (ICD-10 I48) and heart failure (ICD-10 I50). We followed the same methodology (search terms, inclusion criteria, risk of bias evaluation and assessment of the quality of evidence) of the WHO systematic review. Pooled effect estimates were calculated for road, railway, aircraft and mixed noise sources using random effects models. For road traffic noise we investigated potential sources of between-study heterogeneity using meta-regression. We also explored the potential effect of noise exposure assignment precision on the effect estimates. Results: Fifty-three studies were included in the systematic review: 85 % investigated associations for road, 23 % for rail and 30 % for aircraft noise exposure. The papers spanned 15 countries, with the majority (87 %) of studies investigating populations within European countries. In total 35 studies were included in the meta-analyses for heart disease incidence, 28 for mortality and five for prevalence. We found positive associations between long-term exposure to road traffic and aircraft noise and heart disease incidence (relative risk (RR) = 1.02 [95 % confidence interval (CI),1.01 to 1.04]; RR = 1.03 [0.99 to 1.07], per 10 dB increase in Lden, respectively) and between long-term road, rail and aircraft noise exposure and heart disease mortality (RR = 1.03 [ 1.01 to 1.05]; RR = 1.02 [1.02 to 1.03]; RR = 1.07 [1.01 to 1.14], per 10 dB increase in Lden, respectively). The pooled estimates for aircraft noise were attenuated when we excluded small-area studies from the analysis (RR = 1.00 [0.99 to 1.01] for incidence and RR = 1.03 [0.98 to 1.07] for mortality). When combining all sources of transport noise, we found similar pooled effect estimates for heart disease incidence (RR = 1.03 [1.01 to 1.04]) and mortality (RR = 1.03 [1.02 to 1.05]) per 10 dB Lden increase in long-term noise exposure. The starting point for these exposure response relationships was between 32 to 45 dB Lden, depending on the source and outcome. All exposures are at the most-exposed façade. We found suggestive evidence that effects estimates could be higher in studies focused on older adults and in studies using the most precise exposure assignment (noise calculated at the residential address with floor height), although further studies are needed to confirm these findings. Conclusions: The epidemiological evidence on the association between transportation noise and heart disease has increased rapidly since the publication of the WHO Environmental Noise Guidelines in 2018, although the effects of noise from railway and aircraft remain relatively understudied. When including newer studies, we found different exposure response relationships for road traffic noise, and associations between railway and aircraft noise and heart disease mortality. Our results have implications on quantitative health risk assessments that inform policy and decision making. Caution is needed if applying our results to populations and settings outside Europe. Future epidemiological studies should aim to use precise exposure assignment calculated at the residential address, rather than estimating from spatial grids with a coarse spatial resolution.